Pemberdayan Ekonomi Petani Lele Dalam Menuju Ikon Desa Lele (Kasus Desa Senggowar, Kec. Gondang) Kabupaten Nganjuk - Nugrono, Sigit Dwi; Purwadi, Purwadi (Dewan Pimpinan Daerah (DPD) Forum Dosen Indonesia JATIM, 2019)
Senggowar Village is a part of Gondang sub-district, Nganjuk district, a village that wishes to become a village with a ?catfish? icon. Economic problems cause many parents to work outside the home, so that their children are less attention and get along with the environment that is not true. Some people work in agriculture as agricultural laborers, especially primary products with inadequate income. Village officials and community leaders look for solutions in various opportunities by introducing villages with the icon